"You could find a good or a bad provider, I would say you just have to go and see": A qualitative study of the influence of perceptions of service quality on family planning service use in Burkina Faso. - Sarah Castle; Fiacre Bazie; Amelia Maytan-Joneydi; Kindo Boukary; Lisa M Calhoun; Yentema Onadja; Georges Guiella; Ilene S Speizer (PLOS Global Public Health, 2023)
This qualitative study from Burkina Faso explores community-level perceptions of family planning (FP) service quality among FP users and non-users. It examines how perspectives on service quality may influence women's motivation to seek modern methods from health facilities. For this study, twenty focus group discussions were undertaken with non-users and current users of modern FP including unmarried, sexually active women ages 15-19 and 20-24 and ever married women ages 15-24 and 25+ in Bobo Dioulasso and Banfora, Burkina Faso. The findings demonstrate that respondents prioritized a welcoming environment, positive provider-client exchanges, the full provision of information (especially about side-effects), a pain-free experience, a short waiting time, and privacy and confidentiality. Poor service quality did not, in general, reduce women's demand or need to use a FP method. Some women who were reluctant to use formal health services used a non-facility-based method (calendar method, withdrawal, condoms or abstinence). Importantly, many unmarried, younger women and adolescents, who were more likely to be stigmatized by providers, exhibited agency by proactively seeking a method despite the potential for a negative experience. They prioritized their health and wellbeing over and above any interpersonal barriers they were likely to encounter. Incorporating strategies to improve the quality of FP services based on locally defined elements of quality should be a specific programmatic goal. These strategies can be identified through quality assessments employing a woman-centered lens. Women who visit facilities can be encouraged to share their positive experiences with their networks to improve community-level perspectives of facility quality. Improving service quality can attract new users, especially adolescents, and retain those who have already adopted a FP method. Through these multi-pronged actions, women's (and community) expectations and experience of quality can improve. This, in turn, may lead to greater client satisfaction and associated higher FP prevalence.